Sensor Technologies Empowered by Materials and Molecular Innovations - Swager, Timothy M. (Angewandte Chemie International Edition, 2018)
Functional synthetic designer materials can impact many advanced technologies, and the chemical sensor area is intimately reliant on these new chemical innovations. The transduction of chemical and biological signals is necessary for low cost omnipresent chemical sensing and will be realized by chemical designs of new transduction materials. We are poised for many new innovations to empower new generations of sensor technologies. Materials innovations promise to expand the capabilities of present hardware, drive down the cost, and ensure broad implementation of these methods. Sensing materials make sense: The transduction of chemical and biological signals is necessary for low‐cost omnipresent chemical sensing and will be realized by chemical designs of new transduction materials. Materials innovations promise to expand the capabilities of present hardware, drive down the cost, and ensure broad implementation of these methods.